An introduction to global studies - Campbell, Patricia J. (Wiley-Blackwell, 2010)
An Introduction to Global Studies presents readers with a solid introduction to the complex, interconnected forces and issues confronting today's globalized world. Introduces readers to major theories, key terms, concepts, and notable theorists. Equips readers with the basic knowledge and conceptual tools necessary for thinking critically about the complex issues facing the global community. Includes a variety of supplemental features to facilitate learning and enhance readers' understanding of the material.